Between the Land and the River: Some Aspects of the Mandelli Lordship in Piovera (14th-15th Centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The essay focuses on the origin and the content of the Mandelli’s lordship in Piovera, castrum on the Tanaro, in Pavia countryside, that in the 14th-15th centuries was provided with strategic importance because of its position between the Duchy of Milan and southern Piedmont. Based on the pre-eminence of land and in 1450 strenghtend by the promotion of Piovera in comitatus, the exercise of the seigniorial powers by the Mandelli particularly concerned the transit per terram et per aquam, as well as the exploitation of areas near the river. The essay weighs up the amount and the incidence of some land and seigniorial revenues, thanks to documents produced during disputes opposing counts and some competitors about these powers in the 15th century.
Keywords: Rural lordship; Mandelli; water resources; medieval economy